Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Photoluminescence Properties of Ordered Mesoporous ZnO - Chernikov, Alexej; Horst, Swantje; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (The Journal of Physical Chemistry C)
Nanoporous ZnO powders with high surface-to-mass ratios (SMR) between 15 and 70 m2 g−1 are synthesized, structurally characterized, and studied by time-resolved photoluminescence (PL). A strong dependence of the recombination dynamics and spectral width on SMR is observed at T = 10 K, and pronounced disorder-induced effects are found in the temperature dependence. Both the thermally induced shift of the PL maximum and the spectrally integrated PL intensity are interpreted by appropriate theoretical models. This consistent quantitative analysis of the experimental data yields a characteristic energy of 15 meV for the disorder scale in the nanoporous ZnO sample with an intermediate SMR.

Mesoporous In2O3 with Regular Morphology by Nanocasting: A Simple Relation between Defined Particle Shape and Growth Mechanism - Haffer, Stefanie; Waitz, Thomas; Tiemann, Michael (The Journal of Physical Chemistry C)
In2O3 with ordered, uniform mesoporosity is prepared by nanocasting, using various porous silica phases (KIT-6, SBA-15) as structure matrices. The In2O3 particles exhibit well-defined morphologies (spherical or ellipsoidal, depending on the choice of silica matrix) and quite uniform sizes in the range of a few hundred nanometers. The regular morphology of the In2O3 particles is not associated with the morphological properties of the silica matrices. Instead, it is the result of the growth mechanism of In2O3 inside the silica pores; this mechanism is investigated in some detail. Hence, the nanocasting method offers a versatile and simple way of creating mesoporous In2O3 with regular morphology; this will be beneficial for many applications that require well-defined morphological properties, such as gas sensing or catalysis.

Role of Dihydrogen Bonds for the Stabilization of Self-Assembled Molecular Nanostructures - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Chainlike Au−O Structures on Au(110)-(1 × r) Surfaces Calculated from First Principles - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Influence of the Side Group Aromaticity on the Organic Molecule Adsorption on Cu(110) - Rauls, E.; Schmidt, Wolf Gero (Journal of Physical Chemistry C)

Ripening Effects in ZnS Nanoparticle Growth - Tiemann, Michael; Marlow, Frank; Hartikainen, Juha; Weiss, Özlem; Lindén, Mika (The Journal of Physical Chemistry C)
The growth of ZnS nanoparticles during precipitation from aqueous solution is studied by in situ stopped-flow UV absorption spectroscopy at temperatures between 283 and 323 K. Particle growth is marked by substantial ripening during the first 60 ms. Kinetic data suggest that a ripening mechanism by coalescence (oriented attachment) is predominant over Ostwald ripening, although the latter seems to coexist to a significant degree at early temporal stages, predominantly at low temperatures.

The Influence of Catalyst's Oxidation Degree on Carbon Nanotube Growth as a Substrate-Independent Parameter - de los Arcos de Pedro, Maria Teresa; Oelhafen, Peter; Thommen, Verena; Mathys, Daniel (The Journal of Physical Chemistry C)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)